A person-centered approach to the study of commitment - Meyer, John; Stanley, L.; Vandenberg, R. (2013)
Theories of workplace commitment have become increasingly complex with propositions regarding its multiple-component structure (e.g., affective, normative, continuance) and multiple foci (e.g., organization, supervisor, team). To date, most research has taken a variable-centered approach (e.g., regression, SEM) to address the additive and interactive effects of commitment components and foci on behavior and well-being. This assumes that research samples are homogeneous and that the same theoretical framework and empirical findings apply uniformly to employees in general. More recently, it has been proposed that a sample can contain subgroups and that the variables of interest (e.g., commitment components or foci) might combine and relate differently to other variables within these subgroups. Consequently, there has been an increase in the use of person-centered strategies (e.g., cluster analysis, latent profile analysis) to identify and compare these subgroups. We provide an overview of commitment theory and research to demonstrate how use of a person-centered research strategy can provide new insights into the nature and implications of commitment. We also provide a critical evaluation of person-centered strategies with the objective of encouraging greater use of more advanced analytic procedures in future research. Finally, we discuss the benefits of person-centered research for theory and practice.